Mentoring for Textile Liquid Waste Management and Occupational Safety Improvement in Lurik Asri Fabric Center, Klaten - Ahamd Darmawi; Dedy Harianto; Hasna Khairunnisa; Mokh Afifuddin (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2025)
The center of Lurik textile industry in Tlingsing Village, Klaten, Central Java, is one of the distinctive hubs for traditional fabric production in Indonesia. It consists of several households or small and medium-sized enterprises (SMEs) that produce Lurik textiles using traditional methods. This community engagement initiative discusses a mentoring initiative aimed at enhancing sustainable practices and workforce empowerment in the Lurik Asri Weaving Center, Klaten. Through collaboration between educational institutions and local SMEs, the main issues such as wastewater management, Occupational Health and Safety (OHS) implementation, workforce motivation, and technology adoption are identified. The applied methods of education, simulation, and mentoring aim to uncover potentials and enhance the capacities of entrepreneurs. The outcomes include increased understanding and skills, as well as the establishment of sustainable partnerships. Through data mapping and evaluation, this article demonstrates that this initiative not only provides immediate benefits to SMEs but also paves the way for sustainable and inclusive development at the local level.